Third ventriculostomy through the lamina terminalis for intracranial pressure monitoring after aneurysm surgery: technical note - Kraemer Jorge L.; Gobbato Pedro L.; Andrade-Souza Yuri M. (Arquivos de Neuro-Psiquiatria)
OBJECTIVE: A new ventriculostomy technique through the lamina terminalis is described. This technique is applied mainly during aneurysm surgery at the acute stage. METHOD: Thirteen patients were operated on intracranial aneurysms and, during the procedure, had the lamina terminalis fenestrated. A ventricular catheter was inserted into the third ventricule, left in place and connected to an external drainage system for further intracranial pressure (ICP) monitoring and/or cerebrospinal fluid (CSF) drainage. RESULTS: ICP readings and CSF drainage were obtained in all cases. No complication was recorded. CONCLUSION: Third ventriculostomy through the lamina terminalis is a simple and easy technique that can be used as an alternative to conventional ventriculostomy. This procedure can be indicated in cases where the ventricule is not reached by means of another technique, and when the decision to perform ventriculostomy is made at the end of aneurysm surgery.